Carbon dioxide adsorption on biochars produced at different temperatures - Rebitanim, Nur Zalikha (2013)
Biochar has been acknowledged for its unique property which makes it a potential candidate for carbon dioxide adsorbent in soil and adsorbent for carbon dioxide (CO2) in the flue gas system. Although there is a wide range of feedstock and techniques available for biochar production, there have been limited reports on the correlation of its properties by different production method with the effectiveness of the biochar for CO2 adsorption. In this study, the properties of several biochar produced at different temperatures (ranging from 450 to 850°C) from gasification and pyrolysis are being compared. Physiochemical characterization has been performed to characterize the biochar properties. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) were used to evaluate the functional groups and surface morphology of the biochar. Thermogravimetric analyzer (TGA) was used to discover the thermal properties, reactivity during adsorption and kinetic analysis with carbonation model. The biochar are chemically treated with monoethanolamine (MEA) and the adsorption capacity of raw and amine treated biochar are being compared. During the adsorption study, it was observed that raw sawdust pyrolyzed at 850°C and amine treated coconut shell gasified at 800°C gave the highestad sorption of 47.48 and 35.57mgCO2/g sorbent at temperature of 30°C. For adsorption temperature at 70°C, commercialized activated carbon and amine treated coconut shell gave adsorption values of 34.36 and 35.496mgCO2/g accordingly. CO2 adsorption may happen at two different phases whereby physisorption occurs at lower temperature of less than 50°C and physisorption coupled with chemisorption reactions takes place at higher temperature range. The CO2 chemisorption is a complex reaction that is further complicated by heterogeneity of the biochar surface. Although the adsorption capacity may be associated with the surface area of sample, this statement can be further studied whereby samples with low surface area have higher adsorption compared with higher surface area. The presence of some functional groups such as carboxylic acids,quinones and ketones may contribute in the effectiveness of CO2 chemisorption. Nitrogen functionalities and the basicity of samples increased after the amine treatment and is said to assist the adsorption capacity. However its presence does not necessarily increases the CO2 uptake where all treated biochar except coconut shell gives low values of CO2 uptake as compared to raw samples at temperature of 70°C. Therefore the effectiveness of the CO2 adsorption may not only be contributed by the value of the surface area but also the chemical functionalities that appear after the production process and amine treatment. Saturated adsorption model provides a fundamental analysis of the dominant process of each adsorbent. In this study, all biochar has dominant product layer diffusion regime. The product layer diffusion control gives values of 85-99% ultimate adsorption. This may indicate that the CO2 gas has saturated the reacting particle at which the adsorption of CO2 takes place. Therefore the adsorption requires more time to reach its ultimate conversion. Overall, all the objectives has been satisfied and it can be said that biochar has the potential to be used as adsorbent for CO2 and the ability is comparable to the commercial activated carbon. Therefore it is suitable to be applied in industry particularly flue gas system for CO2 adsorption.